2010
DOI: 10.1002/dvdy.22496
|View full text |Cite
|
Sign up to set email alerts
|

IgSF molecule MDGA1 is involved in radial migration and positioning of a subset of cortical upper‐layer neurons

Abstract: *Mdga1, encoding a GPI-anchored immunoglobulin superfamily molecule containing an MAM domain, is expressed by a specific subset of neurons, including layer II/III projection neurons, in the mouse neocortex. To investigate the function of Mdga1 in corticogenesis, we generated Mdga1-deficient mice and backcrossed them to obtain a congenic background. Gross anatomy of the Mdga1-deficient brain at postnatal day (P) 14 showed no obvious phenotype. However, the migration of Mdga1-mutant neurons to the superficial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…Our results replicate previous reports of expression of Cntn6 in anterior thalamic nuclei [74, 75]. Mdga1 is expressed in a layer- and area-specific manner in the cortex [76] and mutation of the gene leads to a delay in cortical neuronal migration [77]. More recently, Mdga1 has also been found to interact with neuroligin-2 to negatively regulate inhibitory synapse formation [78, 79].…”
Section: Resultssupporting
confidence: 91%
“…Our results replicate previous reports of expression of Cntn6 in anterior thalamic nuclei [74, 75]. Mdga1 is expressed in a layer- and area-specific manner in the cortex [76] and mutation of the gene leads to a delay in cortical neuronal migration [77]. More recently, Mdga1 has also been found to interact with neuroligin-2 to negatively regulate inhibitory synapse formation [78, 79].…”
Section: Resultssupporting
confidence: 91%
“…MDGAs are highly expressed in the developing brain (12,15,16). Knockout of MDGA1 causes a discrete phenotype in neuronal migration and impairs rostral growth of commissural axons, suggesting an important role during the initial development of the brain (17,18). Interestingly, SNP-based, large-scale human genetic analyses suggested that MDGA1 and MDGA2 may be susceptibility genes for schizophrenia, bipolar disorder, and autism spectrum disorder (19)(20)(21).…”
mentioning
confidence: 99%
“…It is noteworthy that while Mdga2 over-expression largely rescued the deficit, there was not a complete rescue. Interestingly, Mdga1 , Mdga2 closest homologue, is required for neuronal migration [44], [45]. Thus, while Mdga2 plays a major role in Laf4-regulated migration, it may not be the only effector gene.…”
Section: Discussionmentioning
confidence: 99%